Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C J; Tomás Barberán, F a; Espin, J C; López Carrasco, C; Olivares, A; Rey, a I (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
Keywords: Curculio; fat; fatty acid; iberian pig